Perbedaan Sengaja dan Tidak Sengaja dalam Hukum Pidana - Irawati, Sri Ayu (Ideas Publishing, 2024)
In criminal law, the element of intent is one of the important elements that determines criminal liability. The distinction between acts committed intentionally (dolus) and acts unintentionally (culpa) has significant implications for determining sanctions and the level of guilt of the perpetrator. ‘Deliberately’ refers to an act done with will and full knowledge of the consequences of that act. This includes intentionality as a goal, intentionality as a certainty, and intentionality as a possibility. On the other hand, 'Unintentional' refers to actions that occur due to negligence or carelessness, where the perpetrator does not intend the consequences to occur, but these consequences arise due to a lack of attention or violation of the expected standards of care. These differences are important to identify because they influence the type and severity of punishment, as well as indicating the degree of moral and legal culpability of the perpetrator. This article examines the differences in the concepts of intent and negligence in criminal law, as well as their implications for legal decisions and law enforcement policies.